We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
362
1
avatar

5(x-6)-6(x-5)=x+5-(x-3)

 Aug 17, 2017

Best Answer 

 #1
avatar
+1

Solve for x:
5 (x - 6) - 6 (x - 5) = 8

5 (x - 6) = 5 x - 30:
5 x - 30 - 6 (x - 5) = 8

-6 (x - 5) = 30 - 6 x:
-30 + 5 x + 30 - 6 x = 8

Grouping like terms, -30 + 5 x + 30 - 6 x = (30 - 30) + (5 x - 6 x):
(30 - 30) + (5 x - 6 x) = 8

5 x - 6 x = -x:
-x + (30 - 30) = 8

30 - 30 = 0:
-x = 8

Multiply both sides of -x = 8 by -1:
(-x)/(-1) = -8

(-1)/(-1) = 1:
Answer: | x = -8

 Aug 17, 2017
 #1
avatar
+1
Best Answer

Solve for x:
5 (x - 6) - 6 (x - 5) = 8

5 (x - 6) = 5 x - 30:
5 x - 30 - 6 (x - 5) = 8

-6 (x - 5) = 30 - 6 x:
-30 + 5 x + 30 - 6 x = 8

Grouping like terms, -30 + 5 x + 30 - 6 x = (30 - 30) + (5 x - 6 x):
(30 - 30) + (5 x - 6 x) = 8

5 x - 6 x = -x:
-x + (30 - 30) = 8

30 - 30 = 0:
-x = 8

Multiply both sides of -x = 8 by -1:
(-x)/(-1) = -8

(-1)/(-1) = 1:
Answer: | x = -8

Guest Aug 17, 2017

8 Online Users